Molecular Epidemiology, Evolution and Reemergence of Chikungunya Virus in South Asia - Sharif, Nadim; Sarkar, Mithun Kumar; Ferdous, Rabeya Nahar; Ahmed, Shamsun Nahar; Billah, Md. Baki; Talukder, Ali Azam; Zhang, Ming; Dey, Shuvra Kanti (Frontiers in Microbiology, 2021)
Chikungunya virus (CHIKV) is a vector (mosquito)-transmitted alphavirus (family- Togaviridae). CHIKV can cause fever and febrile illness associated with severe arthralgia and rash. Genotypic and phylogenetic analysis are important to understand the spread of CHIKV during epidemics and the diversity of circulating strains for the prediction of effective control measures. Molecular epidemiologic analysis of CHIKV is necessary to understand the complex interaction of vectors, hosts and environment that influences the genotypic evolution of epidemic strains. In this study, different works published during 1950s to 2020 concerning CHIKV evolution, epidemiology, vectors, phylogeny, and clinical outcomes were analyzed. Outbreaks of CHIKV have been reported from Bangladesh, Bhutan, India, Pakistan, Sri Lanka, Nepal and Maldives in South Asia during 2007-2020. Three lineages- Asian, East/Central/South African (ECSA) and Indian Ocean Lineage (IOL) are circulating in South Asia. Lineage, ECSA and IOL became predominant over Asian lineage in South Asian countries during 2011-2020 epidemics. Further, the mutant E1-A226V is circulating in abundance with Aedes albopictus in India, Bangladesh, Nepal and Bhutan. CHIKV is underestimated as clinical symptoms of CHIKV infection merges with the symptoms of dengue fever in South Asia. Failure to inhibit vector mediated transmission and predict epidemics of CHIKV increase the risk of larger global epidemics in future. To understand geographical spread of CHIKV, most of the studies focused on CHIKV outbreak, biology, pathogenesis, infection, transmission and treatment. This updated study will reveal the collective epidemiology, evolution and phylogenies of CHIKV, supporting the necessity to investigate the circulating strains and vectors in South Asia.